High HBsAg clearance rate and viral dynamics in HBeAg-positive, ALT-normal children and adolescents with chronic HBV infection: results from the prospective sprout project - Xin Wang; Changxiang Lai; Ruiling Li; Jia Lei; Yuyin Xie; Zhiyu Li; Qiyuan Tang; Qing He; Hongfei Zhang; Zheng Zhang; Fang Wang (Emerging Microbes and Infections)
Hepatitis B e antigen (HBeAg)-positive chronic hepatitis B virus (HBV) infection in children and adolescents with normal alanine aminotransferase (ALT) levels constitutes a substantial population in China, yet the optimal timing for antiviral therapy remains unclear. This prospective, real-world study, conducted as the primary centre of the Sprout Project, evaluated the hepatitis B surface antigen (HBsAg) loss rate and viral-immune dynamics of pegylated interferon α (PEG-IFN-α) treatment in 85 chronic HBV patients aged 3–18 years over a 24-month period. A total of 27 HBeAg-positive, ALT-normal patients were selected for analysis. Patients were treated with a combination of PEG-IFN-α and entecavir. After 24 months, the overall HBsAg loss rate was 48.15%, with 47.37% in the immune-tolerant phase and 50% in the grey zone phase. Among those who cleared HBsAg, 84.62% had ALT elevation prior to anti-HBsAg antibody (HBsAb) seroconversion, which occurred 28–400 days before HBsAg loss. While HBsAg and HBV DNA were cleared by 24 months in the HBsAg loss group, 23.08% of children remained HBeAg-positive. Notably, 61.54% developed detectable HBsAb prior to HBsAg loss. Children aged 3–7 years had significantly higher clearance rates than those aged 8–18 years. These findings support the effectiveness of PEG-IFN-α combined with nucleos(t)ide analogs in achieving high HBsAg loss rates in young, HBeAg-positive, ALT-normal chronic HBV children and adolescents, with immune activation potentially preceding ALT elevation, and offers valuable insights into the viral-immune dynamics during treatment, highlighting the potential of antiviral therapy in this population.